A novel nano-emulsion cream of casein isolated from raw milk for thermal and acid burn wounds - Shivani Shrivastava; Saumya Das; Chanchal Sharma; Archna Singh; Sanjita Das; Manas Kumar Das; Pankaj Kumar Tyagi; Navneet Khurana (Brazilian Journal of Pharmaceutical Sciences)
Abstract Traditionally, raw cow milk has been employed to treat acid and thermal burns due to its antibacterial, antibiotic, and antifungal properties. It also aids in preventing scarring and alleviating burn-related skin discomfort. This study focuses on evaluating a nanoemulsion cream made from casein extracted from raw cow milk for managing acid and thermal burns. Casein was isolated and used to create 2%, 5%, and 10% w/w nanoemulsion creams. Wistar albino rats were used to induce acid and thermal burns, and the healing progress was monitored by measuring wound contraction and epithelialization period. The results demonstrated significant wound healing effects of the casein creams (p<0.001) in acid burns, with the 10% w/w cream showing the highest epithelization rate in thermal burns. Raw milk also exhibited notable healing properties in acid burns. However, its effectiveness was relatively lower in thermal burns. This study suggests that raw milk and its casein-derived creams could be utilized as first-aid treatments for acid burns, though they may be less effective for thermal burns.